Elizabethkingia anophelis outer membrane vesicles as a novel vaccine candidate against infection: insights into immune response and potential for passive immunity - Ya-Sung Yang; Hung-Jui Chen; Xiao-Chun Chen; Hung-Jen Tang; Fang-Ju Chang; Yun-Ling Huang; Yu-Ling Pan; Dinesh Kumar Kesavan; Huan-Yuan Chen; Hung-Sheng Shang; Shu-Chen Kuo; Te-Li Chen; et al. (mSphere, 2023)
ABSTRACTThe emerging pathogen Elizabethkingia anophelis poses severe threats to public health and has caused several outbreaks. The efficacy of antimicrobials is limited due to the pathogen’s innate multi-drug resistance to most antibiotics. Hence, novel approaches to treat E. anophelis infections are urgently needed. This study evaluated the immunogenic and protective effects of the imipenem-induced outer membrane vesicles (iOMVs) of E. anophelis as a vaccine. Mice immunized with iOMVs were completely protected during lethal-dose challenges. Passive immunization with hyperimmune sera and splenocytes conferred protection against lethal pneumonia. iOMVs also induced Th1-, Th2-, and Th17-driven immune responses. Immunization with iOMVs increased IgG1 and IgG2c isotype levels, and the antisera from immunized mice promoted complement-dependent bactericidal and opsonophagocytic activities against E. anophelis C08. Our study suggests that E. anophelis iOMVs are a promising vaccine candidate for preventing and treating E. anophelis infections and provides insights into the use of OMVs in vaccine development against the clinically emergent E. anophelis.IMPORTANCEElizabethkingia anophelis, a Gram-negative pathogen, causes infections such as bacteraemia, pneumonia, and neonatal meningitis. The pathogen resists most antimicrobial classes, making novel approaches urgently needed. In natural settings, Gram-negative bacteria secrete outer membrane vesicles (OMVs) that carry important molecules in the bacterial life cycle. These OMVs are enriched with proteins involved in virulence, survival, and carbohydrate metabolism, making them a promising source for vaccine development against the pathogen. This study investigated the efficacy of imipenem-induced OMVs (iOMVs) as a vaccine candidate against E. anophelis infection in a mouse pneumonia model. Mice immunized with iOMVs were completely protected during lethal-dose challenges. Passive immunization with hyperimmune sera and splenocytes conferred protection against lethal pneumonia. Further investigation is needed to understand the mechanisms underlying the protective effects of iOMV-induced passive immunity, such as the action on specific antibody subclasses or T cell subsets.